Tafsir Idariah Manajemen Sumber Daya Manusia dalam QS. Al-Baqarah [2]: 30-39 - Akbar, Ach. Hanuji; Arifin, Zainal; Jamaludin, Muhamad; Mentari, Inggi Eka Ria (Jurnal Pendidikan Madrasah, 2024)
This study aims to analyse the concept of Human Resource Management (HRM) in Q.S. Al-Baqarah [2]:30-39. This research will reveal the meaning and relevance of these verses in the context of human resource management in Islamic educational institutions. This research uses a literature study method, analysis is carried out on various relevant literature to understand the roles and responsibilities of human resources in accordance with Islamic teachings. The results of the study show that effective human resource management includes several important aspects, including planning, selection and placement, development (training), and compensation. Human resource management from the perspective of the Quran, especially in the story of the Prophet Adam (as). (QS. Al-Baqarah [2]: 30 39) shows that the quality of good human resources greatly contributes to the achievement of optimal educational goals. In addition, the concept of caliph requires each individual to have adequate knowledge and skills to carry out his duties. Therefore, this study recommends that Islamic educational institutions apply the principles of HRM based on Islamic values in daily practice.